2014
DOI: 10.1371/journal.pone.0084636
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Antiproliferative and Differentiating Responses of Hepatocarcinoma Cells to Subthermal Electric Stimulation

Abstract: Capacitive Resistive Electric Transfer (CRET) therapy applies currents of 0.4–0.6 MHz to treatment of inflammatory and musculoskeletal injuries. Previous studies have shown that intermittent exposure to CRET currents at subthermal doses exert cytotoxic or antiproliferative effects in human neuroblastoma or hepatocarcinoma cells, respectively. It has been proposed that such effects would be mediated by cell cycle arrest and by changes in the expression of cyclins and cyclin-dependent kinase inhibitors. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 46 publications
4
62
0
Order By: Relevance
“…Indeed, our late passage cells showed a number of genetic abnormalities, including aneuploidy (data not shown) that are characteristic of senescent cultures. The possibility that CRET elicits antiproliferative effects in senescent ADSC could take partial support from previous studies by our group, which report that CRET treatment causes antiproliferative effects in hepatocarcinoma HepG2 and neuroblastoma NB69 [32,33,34,35,36], two human cancer cell lines known to carry a variety of genetic alterations [52,53]. …”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Indeed, our late passage cells showed a number of genetic abnormalities, including aneuploidy (data not shown) that are characteristic of senescent cultures. The possibility that CRET elicits antiproliferative effects in senescent ADSC could take partial support from previous studies by our group, which report that CRET treatment causes antiproliferative effects in hepatocarcinoma HepG2 and neuroblastoma NB69 [32,33,34,35,36], two human cancer cell lines known to carry a variety of genetic alterations [52,53]. …”
Section: Discussionmentioning
confidence: 73%
“…For sham-exposure, the electrode pairs inserted in control dishes were also connected to the generator, but not energized. The stimulation pattern consisted of 5-minute pulses of 448 kHz sine wave current, at a subthermal density of 50 μA/mm 2 , separated by 4-h interpulse lapses, along a total period of 48 h. Such exposure parameters have been proven to affect cell proliferation in previous studies by our group [32,33,34,35,36]. The cultures were grown in two separate, identical CO 2 incubators (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proionic effects or proionic system is the name given to the set of phenomena that take place at cellular level and lead to the restoration of the cell membrane's normal potential, as well as the ionic balance established through the cell membrane. Although radiofrequency (RF) has been and is traditionally used for its thermal effects, Hernández-Bule et al [2,3,4,5,6] have described effects resulting from subjecting various tissues to a 448 kHz electromagnetic field at intensities which are not capable of heating such tissues, showing the occurrence of molecular phenomena other than those caused by the well-known classic thermal effects. Among these, proionic phenomena stand out.…”
Section: Introductionmentioning
confidence: 99%
“…Capacitive-resistive electric transfer (CRet) system applies electric currents at frequencies within the 0.4-0.6 MHz range to treatment of inflammation and musculoskeletal injuries [16][17][18][19]. It has been demonstrated that CRet system, which can produce electric stimuli and thermal effects simultaneously in tissues, can induce synergistically cytostatic and/ or cytotoxic effects in tumor tissues [20,21].…”
mentioning
confidence: 99%